Recent Progress on PZT Based Piezoelectric Energy Harvesting Technologies - Kang, Min-Gyu; Jung, Woo-Suk; Kang, Chong-Yun; Yoon, Seok-Jin (Actuators, 2016)
Energy harvesting is the most effective way to respond to the energy shortage and to produce sustainable power sources from the surrounding environment. The energy harvesting technology enables scavenging electrical energy from wasted energy sources, which always exist everywhere, such as in heat, fluids, vibrations, etc. In particular, piezoelectric energy harvesting, which uses a direct energy conversion from vibrations and mechanical deformation to the electrical energy, is a promising technique to supply power sources in unattended electronic devices, wireless sensor nodes, micro-electronic devices, etc., since it has higher energy conversion efficiency and a simple structure. Up to now, various technologies, such as advanced materials, micro- and macro-mechanics, and electric circuit design, have been investigated and emerged to improve performance and conversion efficiency of the piezoelectric energy harvesters. In this paper, we focus on recent progress of piezoelectric energy harvesting technologies based on PbZrxTi1-xO3 (PZT) materials, which have the most outstanding piezoelectric properties. The advanced piezoelectric energy harvesting technologies included materials, fabrications, unique designs, and properties are introduced to understand current technical levels and suggest the future directions of piezoelectric energy harvesting.